Perioperative aspirin and long-term survival in patients undergoing coronary artery bypass graft. Issue 1 (December 2018) - Ding, Qian; Liu, Hong; Zhang, Zugui; Goldhammer, Jordan; Yuen, Eric; Li, Zhongmin; Yao, Linong; Young, Nilas; Boyd, Douglas; Weintraub, William; Morris, Rohinton; Sun, Jianzhong
Abstract This study aimed to examine association between perioperative uses of aspirin and long-term survival in patients undergoing CABG. A retrospective cohort study was performed in 9, 584 consecutive patients receiving cardiac surgery from three tertiary hospitals. Of all the patients, 4, 132 patients undergoing CABG met inclusion criteria and were divided into four groups: with or without preoperative or postoperative aspirin respectively. 30-day postoperative and long-term mortality were compared with the use of propensity scores and inverse probability weighting adjustment to reduce the treatment-selection bias. The patients taking preoperative aspirin presented significantly more with comorbidities. However, the results of this study showed that preoperative aspirin (vs. no preoperative aspirin) was associated with significantly reduced the risk of 30-day mortality in the patients undergoing CABG. Further, the results of long-term mortality showed that the patients taking preoperative aspirin and postoperative aspirin (vs. not taking) were associated with significantly reduced the risk of 4-year mortality (14.8% vs. 18.1%, RR: 0.82, 95% CI: 0.75–0.89, P = 0.005; 10.7% vs. 16.2%, RR: 0.66, 95% CI: 0.50–0.82, P = 0.003). In conclusion, this cohort study showed that perioperative (before and after surgery) use of aspirin was associated with significant reduction in 30-day mortality without significant bleeding complications, also improved long-term survival in patients undergoing CABG.